Exploring mathematical concepts in six traditional cultural objects: an ethnomathematical perspective - Loviana, Selvi; Sutiarno, Sugeng; Ariyani, Farida; Sowiyah; Hariri, Hasan; Sunyono; Siregar, Rabiyatul Adawiyah; Nurhanurawati (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to explore mathematical concepts embedded in six traditional cultural objects and to examine how these concepts can contribute to contextual mathematics learning through an ethnomathematical perspective. Method: This research employed a qualitative ethnomathematical approach to identify mathematical elements contained in selected cultural artifacts. Data were collected through observation, documentation, and literature analysis of six traditional cultural objects. Each object was examined to identify implicit mathematical structures, including geometric forms, symmetry, spatial relationships, numerical patterns, and proportional reasoning. The analysis focused on interpreting how these mathematical ideas are represented within the design, structure, and functional aspects of the cultural objects. Findings: The results reveal that the six cultural objects contain various mathematical concepts such as geometric shapes, symmetry, measurement, patterns, and proportional relationships. These concepts are reflected in the structural composition, decorative motifs, and spatial arrangements found within the artifacts. The analysis demonstrates that cultural objects can represent mathematical ideas in a concrete and meaningful way, making them relevant resources for mathematics learning. Significance: This study provides evidence that cultural artifacts contain valuable mathematical knowledge that can support culturally responsive mathematics education. The findings highlight the potential of ethnomathematics to bridge cultural knowledge and formal mathematics learning, thereby enhancing students’ conceptual understanding while fostering appreciation for local cultural traditions.